2009
DOI: 10.1007/s00401-009-0618-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of the microvascular compartment in multiple sclerosis using laser microdissected blood vessels

Abstract: The blood brain barrier (BBB) is formed by capillary endothelial cells with inter-endothelial cell tight junctions and other cells such as pericytes and astrocytes present. Previous studies have shown a role for tight junction abnormalities in BBB leakage in multiple sclerosis (MS) brain. This marks a key stage in the development of inflammatory demyelination in MS. The aim of this study was to identify aberrantly expressed genes involved in BBB changes in MS lesions. A focused endothelial cell biology microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…An increasing number of studies in a range of neurological diseases have used this approach to identify disease-relevant, cell-specific gene expression changes (Boone et al, 2013, Chu et al, 2009, Kumar et al, 2013, Pietersen et al, 2009, Simpson et al, 2011, Baker et al, 2015. To date, only two studies have employed LCM in the investigation of human MS cases: one identifying gene expression changes in total extracts from NAWM, peri-lesional and lesional regions compared to control WM (Mycko et al, 2012) and the other identifying transcriptomic changes in the vascular compartment in MS (Cunnea et al, 2010); with neither study specifically assessing changes in the astrocyte transcriptome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies in a range of neurological diseases have used this approach to identify disease-relevant, cell-specific gene expression changes (Boone et al, 2013, Chu et al, 2009, Kumar et al, 2013, Pietersen et al, 2009, Simpson et al, 2011, Baker et al, 2015. To date, only two studies have employed LCM in the investigation of human MS cases: one identifying gene expression changes in total extracts from NAWM, peri-lesional and lesional regions compared to control WM (Mycko et al, 2012) and the other identifying transcriptomic changes in the vascular compartment in MS (Cunnea et al, 2010); with neither study specifically assessing changes in the astrocyte transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two studies have combined LCM with microarray analysis in MS research, including analysis of the gene expression profile of blood vessels (Cunnea et al, 2010) and LCM-ed areas of MS lesions and NAWM (Mycko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite promising hope in metalloproteinases as therapeutic targets, use of general inhibitors of metalloproteinases in clinical trials did not yield effective outcome (16), indicating that more detail and systematic analysis * This work was supported, in whole or in part, by National Institutes of Health of the role of metalloproteinases is necessary. Interestingly, brain ischemia is reported to stimulate the permeability of the BBB by promoting disruption of tight junction complex via activation of MMP2 and -9 (17)(18)(19)(20). In other studies, MMP3, -8, and -9 were shown to be able to cleave Occludin, a key protein controlling the tight junction (21)(22)(23).…”
mentioning
confidence: 99%
“…Endothelial α5β1 integrin, involved in endothelial proliferation in hypoxic conditions [87], is transiently upregulated in EAE [40]. Gene expression analysis of the lasercaptured microvascular compartment of active lesions from MS autopsy samples has shown an increased expression of matrix metalloprotease-14 (MMP-14), MMP-2, ADAM17, VEGF-A, and VEGF-R1 [88]. Other inflammatory mediators such as TNF-α, IL-8, transforming growth factor-β (TGF-β), and MMP-9 released by immune cells induce angiogenesis [51] and, in turn, new vessel walls are easily permeable to immune cell transmigration and foster adhesion and cytokine molecules expression [89].…”
Section: Other Angiogenic Molecules Potentially Involved In Ms and Eamentioning
confidence: 99%